2014
DOI: 10.1007/s00128-014-1278-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Polycyclic Aromatic Hydrocarbons in Emissions of Different Mosquito Coils

Abstract: Emission rates and emission factors of particulate matter and polycyclic aromatic hydrocarbons (PAHs) were determined in the emissions of three prevalent mosquito coil brands available in the market in India, under controlled conditions in an environmental chamber. The emission rates varied between the brands and ranged between 2.0 ± 1.9 to 27.1 ± 1.5 μg h(-1) for brand A, 3.4 ± 1.1 to 32.3 ± 1.2 μg h(-1) for brand B and 3.1 ± 1.0 to 72.2 ± 1.1 μg h(-1) for brand C for different compounds. Five and six ring PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 14 publications
1
12
1
Order By: Relevance
“…A segment weighing ~3.0 g was broken off from one end of fine particulate matter (PM) which may deposit in the lungs. This PM contains heavy metals as well as organic chemicals of concern (Chang and Lin 1998;Dubey et al 2014;Lee and Wang 2006;Yang et al 2012). Exposure to PM and its associated chemicals may contribute to acute and chronic respiratory diseases, such as pneumonia and asthma, as well as to various toxic chemical responses (Lin and Shen 2005;Liu et al 2003Liu et al , 1987Roy et al 2009;Shu-Chen et al 2008;Singh et al 2012).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A segment weighing ~3.0 g was broken off from one end of fine particulate matter (PM) which may deposit in the lungs. This PM contains heavy metals as well as organic chemicals of concern (Chang and Lin 1998;Dubey et al 2014;Lee and Wang 2006;Yang et al 2012). Exposure to PM and its associated chemicals may contribute to acute and chronic respiratory diseases, such as pneumonia and asthma, as well as to various toxic chemical responses (Lin and Shen 2005;Liu et al 2003Liu et al , 1987Roy et al 2009;Shu-Chen et al 2008;Singh et al 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Lin and Shen 2005;Liu et al 1987Liu et al , 2003Chang and Lin 1998;Lee and Wang 2006;Shu-Chen et al 2008;Roy et al 2009;Zhang et al 2010;Phal 2011;Singh et al 2012;Dubey et al 2014;Yang et al 2015), very limited studies have analyzed the chemical composition of mosquito coils (e.g. Liu et al 1987;Phal 2011).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PAHs concentration in vapour and particulate phases of mosquito coil smoke has been studied by a few. Dubey et al (2014) reported that in three mosquito coil brands available in India, five and six ring PAHs were not detected while three-ring PAHs contributed about 24%, 42% and 29% and four ring compounds contributed about 53%, 35% and 61% to ΣPAH in coil smoke. Zhou et al (2009) detected all, except one, of 16 USEPA recommend PAHs in coil smoke of eight mosquito coils sourced from China.…”
Section: Pahs In Coil Ashmentioning
confidence: 98%
“…Liu et al (2014) found that essential oilbased mosquito repellent products can generate ultrafine particles and ozone. Not only are these particles more likely to reach and accumulate in human lung alveoli tissue, they also contain a higher concentration of particulates constituting a larger surface area to which harmful substances, such as heavy metals (Cd, Zn and Pb), aldehyde, allethrin, and polycyclic aromatic hydrocarbons (PAHs) can attach (Liu et al, 1987;Chang and Lin, 1998;Liu et al, 2003;Lee and Wang, 2006;Zhang et al, 2010;Dubey et al, 2014;Yang et al, 2015). Harmful health effects may be related to the high concentration of particulates and chemicals attached to the particles.…”
Section: Introductionmentioning
confidence: 99%